A study on the use of artificial intelligence for building digital profiles of printing equipment - Azarenkov, V. I.; Deineko, Zh. V. (ТОВ «Друкарня Мадрид», 2025)
The issue of researching the possibilities and identifying effectiveness of the approximation application of measured data using artificial neural networks in constructing color profiles of printing equipment is raised. Problems and ways to solve them are highlighted. An analysis of the features of converting one color model into another based on the construction of ICC profiles was conducted.
Keywords: artificial intelligence; color